Penggunaan Batok Kelapa sebagai Alat Tukar ditinjau dari Teori ‘Urf dan Undang-Undang No.7/2011 - Novita Dwi Safitri; Andi Wicaksono (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This research aims to analyze the practice of using coconut shells as a medium of exchange in buying and selling at Bahulak Market, Karungan, Plupuh, Sragen from the perspective of 'urf. This research methodology uses a type of field research with a descriptive qualitative approach. The data sources used are primary data and secondary data. The research site is Bahulak Market, Karungan Village, Plupuh District, Sragen Regency. By using data collection techniques in the form of observation, interviews and documentation. The result of this research is the practice of buying and selling is in accordance with the pillars and conditions of buying and selling according to sharia with a medium of exchange in the form of coconut shell. This coconut shell meets the criteria of a medium of exchange. From the perspective of ‘urf, this buying and selling is included in al-‘urf as-ṣaḥīḥ, al-‘urf al-‘amalī, and al-‘urf al-khāṣ which can be used as a legal basis. This buying and selling practice does not violate Law No. 7/2011 on Currency because coconut shells can only be used as a medium of exchange and cannot be considered money or currency.